Assessment of level of knowledge on cardio-Pulmonary resuscitation among nurses - JASILA ABRAHAM; D.CAROLINE MARY (International Journal of Pharma and Bio Sciences, 2016)
Cardiac arrest is fatal if prompt and immediate treatment is not given and is considered as a medical emergency. It is documented that sudden cardiac arrest can be managed by a timely performed cardio pulmonary resuscitation (CPR). The CPR guidelines are revised periodically by American Heart Association (AHA) and the latest revision was made in the year 2010. Nurses are expected to update their knowledge on CPR as per AHA’s revision to ensure quality patient care. This study aimed to assess the knowledge on revised cardio-pulmonary resuscitation guidelines among nurses. A descriptive cross sectional study design was adopted for the present study. The data were collected from 100 nurses after explaining the purpose of the study and obtained informed consent from them. Self-developed questionnaires which consist of 30 questionnaires were used to collect the data. The results showed that 54% of nurses had moderately adequate knowledge and 46% of them had inadequate knowledge on cardio-pulmonary resuscitation. The present study revealed that the nurses lack adequate knowledge on CPR. Since, nurses spent most of their time in direct patient care; they are the ones who are readily available to manage emergency situations. Hence, she should be knowledgeable and skillful enough in performing emergency medical procedures. Assessing the level of knowledge among nurses help the nurse educators to organize the in-service education and CNE programme which help to improve their knowledge to keep pace with the health care demand.